Analisis Pengaruh Strategi Brand extension terhadap (re)purchase intention dan e-WOM intention Nasabah Bank BCA Xena Maharani - Xena Maharani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
One of the industries that Covid-19 is a "good accelerator" for is the banking industry, which is rapidly adopting new technologies and digitalizing its operations. The banking sector in particular, as well as other financial services industries generally, are shifting more and more towards online and digital value generation due to the rapid advancements in technology. This study aims to examine how the brand extension strategy of the parent brand influences the purchase intention and e-WOM intention of customers on brand extensions in the banking industry, specifically Bank BCA. This relationship is mediated by brand perceived value of the brand extension. Data were collected using an online survey to Bank BCA customers and 255 responses were successfully gathered for further data analysis. This study employed a structural equation modelling (SEM) using Smart-PLS to test the hypotheses. As a result, brand attitude and brand loyalty of Bank BCA have a positive and significant effect on brand perceived value of Bank BCA Digital. Brand perceived value of Bank BCA Digital has a positive and significant effect on (re)purchase intention and e-WOM intention of Bank BCA Digital.